2014
DOI: 10.1111/jfs.12102
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Ethanol Extracts of Rhus javanica and Terminalia chebula Against Shigella Species

Abstract: This study investigated the antimicrobial activities of Oriental medicinal plant extracts against four Shigella species, i.e., Shigella sonnei, Shigella flexneri, Shigella boydii and Shigella dysenteriae. Twelve Oriental medicinal plants were extracted with 80% ethanol. When the Rhus javanica extract was used at 0.01% concentration, 98.09% of the S. sonnei cells were injured. And S. boydii showed significantly different percentages of injured cells at 0.01% and 0.5% of R. javanica extracts, and S. dysenteriae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A study conducted inMRSA, revealed that extract of Rhus javanica inhibitedthe bacterial growth by significantlydecreasing the expression ofmecA, sea, agrA and sarA gene [10]. Another studyshowed that, extract showed inhibitory effect against shigellosis causing pathogens,Shigella flexneri and Shigella dysenteriae,like other bacterial pathogens [14].…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted inMRSA, revealed that extract of Rhus javanica inhibitedthe bacterial growth by significantlydecreasing the expression ofmecA, sea, agrA and sarA gene [10]. Another studyshowed that, extract showed inhibitory effect against shigellosis causing pathogens,Shigella flexneri and Shigella dysenteriae,like other bacterial pathogens [14].…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted in MRSA, revealed that extract of Rhus javanica inhibited the bacterial growth by significantly decreasing the expression of mecA, sea, agrA and sarA gene [10]. Another study showed that, extract showed inhibitory effect against shigellosis causing pathogens,Shigella flexneri and Shigella dysenteriae, like other bacterial pathogens [14].…”
Section: Discussionmentioning
confidence: 99%
“…has been reported from different parts (root, stem, gallarhois) of R. chinensis. 9,[15][16] Recently, antibacterial activity of R. chinensis against methicillin-resistant Staphylococcus aureus, 6 Shigella species 17 and Streptococcus iniae 18 is reported. R. chinensis extract was identified as the most effective anti-inflammatory and anti-photoaging agent.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial activity of the fruits has never been reported though the leaves had displayed antimicrobial activity. 6,[17][18] The phytochemicals present in the plant material were also investigated by chemical tests and GC-MS analysis to identify the biologically active phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation